Duwamish materials, C. F. Voegelin Papers - Voegelin, C. F. (Charles Frederick), 1906-1986; Ransom, Jay Ellis, 1914-; Siddle, Julia (1945)
Three items relating to the Duwamish (Southern Puget Sound Salish) language have been identified in the C. F. Voegelin Papers. They are all in Subcollection II. Materials include correspondence with Jay Ellis Ransom regarding Duwamish, Aleut, and Flathead in Series I. Correspondence; a folder of Ransom's Duwamish Salish material including texts in Salish and English, with linguistic analysis ("Basket-Woman," "Duwamish Text II," and "Duwamish Text III," recorded from Mrs. Julia Siddle at the Muckleshoot Reservation in 1936) in Series II. Research Notes, Subseries VIII. Undetermined Phylum Affiliation; and Ransom's essay "Pronomial System in Duwamish Salish" (1945) in Series IV. Works by Others. Researchers might also be interested in the general Salishan entry for the Voegelin Papers.